2002
DOI: 10.1590/s0103-50532002000500029
|View full text |Cite
|
Sign up to set email alerts
|

Additional Coumarins from Kielmeyera reticulata

Abstract: Do extrato hexânico e da fase extraída com diclorometano do extrato metanólico de Kielmeyera

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Despite 4-alkyl and 4-phenyl coumarins having been identified as the major constituents of some species that occur mainly in the cerrado (Gottlieb et al, 1969;Gottlieb & Stefani, 1970) and restinga (Cruz et al, 2002;Nogueira et al, 2008) and xanthones from species collected in the atlantic forest (Garcia-Cortez et al,1998;Pinheiro et al, 2003a), K. variabilis did not demonstrate the same pattern as observed by previous studies. The presence of flavonoids in this species is in agreement with previous reports from other genera in the Calophylleae tribe as Caraipa (Silveira et al, 2010), Mesua (Banerji & Chowdhury, 1993) and Calophyllum (Cechinel et al, 2009).…”
Section: Resultsmentioning
confidence: 57%
“…Despite 4-alkyl and 4-phenyl coumarins having been identified as the major constituents of some species that occur mainly in the cerrado (Gottlieb et al, 1969;Gottlieb & Stefani, 1970) and restinga (Cruz et al, 2002;Nogueira et al, 2008) and xanthones from species collected in the atlantic forest (Garcia-Cortez et al,1998;Pinheiro et al, 2003a), K. variabilis did not demonstrate the same pattern as observed by previous studies. The presence of flavonoids in this species is in agreement with previous reports from other genera in the Calophylleae tribe as Caraipa (Silveira et al, 2010), Mesua (Banerji & Chowdhury, 1993) and Calophyllum (Cechinel et al, 2009).…”
Section: Resultsmentioning
confidence: 57%
“…Kielmeyera reticulata Saddi is an endemic shrub of Bahia State, Brazil, and prior studies with extracts from its stems revealed the presence of mainly prenylated 4-phenyl and 4-alkylcoumarins. , The present study describes the purification of four new chromenones, named kielmeyerones A–D ( 1–4 ) (Figure ), for which the structures are related to 4-alkylcoumarins found in this and other species of the Kielmeyera genus. Moreover, its anti-inflammatory and antinociceptive properties have been described for the first time.…”
mentioning
confidence: 72%
“…Because the chemical profile of this genus is characterized by the occurrence of phenolic compounds such as xanthones, 4‐phenyl, and 4‐alkylcoumarins (Garcia Cortez et al ., ; Cruz et al ., ; Cruz et al ., ; Scio et al ., ; Nogueira et al ., ) and on the basis of the results by HPLC‐DAD analysis, we suggest that these compounds could be present in the methanolic extract from stems of K . rugosa (MEKR).…”
Section: Discussionmentioning
confidence: 99%